COMPARATIVE ANALYSIS OF CHILDREN’S GAMES IN ENGLISH AND UZBEK FAIRY TALES - Muhammadjonova Ma'muraxon Muhsinjon qizi; Otabek Mukhamadovich Fayzulloyev. (TADQIQOTLAR, 2025)
Annotation: This article presents a comparative analysis of children’s games reflected in English and Uzbek fairy tales. The study explores how traditional games are represented in the folklore of both nations, emphasizing their cultural, educational, and social functions. By examining selected fairy tales, the paper highlights similarities and differences in the symbolic meanings of games, their role in shaping moral values, and their contribution to children’s imaginative development. The findings demonstrate that children’s games in both English and Uzbek fairy tales serve not only as a source of entertainment but also as an important tool for transmitting cultural heritage and ethical principles to younger generations.